Metafora Maknawi dan Universalitas Bahasa Alquran: Studi Linguistik Bahasa Arab - Al-Rasyid, Harun (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2018)
Among the features of the miracles of the Qur’an is on its perfection of language and meaning that includes in the study of linguistics (al-durus min jihhat al-lughah). The linguistics can be seen, for example, from the aspect of style, the broad meaning of words and sentences that have meanings beyond their literal significance. One of the literary styles of the Qur’an that often used is the metaphors (isti‘arah) which is an integral part of the study of al-majaz al-lughawi. Many scholars argue that this metaphorical aspect of the Qur’an closely related to the function of beautifying word structure. On the other hand, this article aims to show that the metaphorical aspect of the Qur’an has several strategic functions, including to build and expand an idea that was previously unthinkable and to broaden the idea of a living order comprehensively. By discussing linguistic studies from the aspect of majazi (metaphor) and the elaboration of the meaning of the word (al-taghayyur al-dala’il) in the Qur’an, this article, therefore, confirms the universality and flexibility of the Qur’anic language.